CORRELATION RESPONSE TIME TRIAGE AND LENGTH OF STAY IN HEAD INJURED PATIENTS IN THE EMERGENCY ROOM OF RSD DR. SOEBANDI - Darotin, Rida; Linafatul, Zunaidah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Head injuries require early in preventing disability or death. Length of stay in the emergency room is the length of health service measured from the time the patient arrives until the patient is transferred to another unit. The purpose of this study was to analyze the relationship between triage response time and length of stay of head injured patients in the emergency department. Method: The research design used a correlational study with a cross-sectional approach. There were 31 respondents who used accidental sampling in the RSD emergency room. dr. Soebandi Jember. The research instrument used an observation sheet and a stopwatch. Result:Most of the triage response times were according to the standards, the length of stay was mostly according to the standards. Fisher Exact Test, p value = 0.008 with a calculated Correlation Coefficient of 0.525, meaning that there is an adequate relationship between the triage response time and the length of stay in head injured patients, the faster the response time in head injured patients, the longer the hospitalization, the management of patients with appropriate, and the selection of the right triage, especially in the management of head injured patients can optimize the recovery of head injuries